VERIFICATION TAXONOMY OF TEACHERS IN TERMS OF THEIR APPROACHES TO AND VIEWS ON ICT TOOLS - Milan, KLEMENT (Trends in education, 2018)
Is it possible to categorize teachers by their approach to modern technology? Are there groups of teachers who use modern technology uncritically? On the contrary, is there a larger group of teachers and educators who actively oppose this use? These are some of the questions which the submitted paper attempts to find the answer to. Based on the aforementioned assumptions, we proceeded to analyze the methods and approaches to the use of ICT tools by the teachers at primary and secondary schools with using pedagogical research methods. The acquired research data was subjected to statistical analysis using multidimensional statistical methods to verify whether the existing teachers' taxonomy by E. Rogers, the teaching staff member in terms of their access to ICT tools, is still valid or needs to be revised.
Keywords: modern technologies; ICT tools; teachers' taxonomy.